A historical analysis of the rejection of persons with disabilities in the world and its reflections in brazilian criminal law (Research, Society and Development, 2022)
The present study aims to address how people with disabilities were victims of society even in the face of their vulnerability, so they were attacked through moral and religious beliefs. To understand how such people suffered - and still suffer - such prejudice, it was necessary to carry out a historical survey from the archaic period to the present Brazilian Democracy, starting to understand how the Federal Constitution of 1988 sought to repair such inequality. In the same sense, it was necessary to investigate the evolutionary process of Criminal Law, which became a reflection of the societal vision in relation to the disabled person, which previously compared in all cases the disabled person as an agent with a high level of dangerousness. Thus, it will be noted that the Statute of Persons with Disabilities was an essential instrument for the realization of the dignity of the human person, which lists several acts now considered as criminal conduct, among them, we highlight: discrimination due to disability and abandonment of the person with a disability. At the same time, it can be seen that in addition to criminal protection, people with disabilities were granted rights that were previously guaranteed to the entire population. For the elaboration of the present work, the deductive methodology was used, supported by the bibliographic research.